2018
DOI: 10.1021/acs.joc.8b01387
|View full text |Cite
|
Sign up to set email alerts
|

Radical Arene Addition vs Radical Reduction: Why Organometal Hydride Chain Reactions Stop and How To Make Them Go

Abstract: Nonideal kinetic chain analysis was used to examine the kinetic limitations of free-radical synthesis. Homolytic aromatic substitution (HAS: ArH + R → ArR + H) occurs in a chain-terminating side reaction to the tributyltin hydride ( SnH) reduction chain (RX + SnH + ( i) → RH + SnX). Kinetic modeling of premixed and slow reagent addition reactions have clarified the mechanisms of SM HAS, with the azo initiator ( iNN i) acting not only as radical source but also (as an H acceptor) as the redox catalyst for aroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…For example, recent mechanistic studies into "classical" reactions involving tin hydrides have revealed fascinating complexity and paved the way to rational development of improved reaction protocols. [14][15][16][17][18][19] The addition of antimony hydrides (primary or secondary stibines) to multiple bondshydrostibination -has been explored to a very limited extent, 20, 21 with well-defined examples being restricted to cases that proceed under Lewis-acid or radical-initiator (azobisisobutyronitrile, AIBN) mediated conditions. 22,23 As part of our exploration into new structure and reactivity at antimony and bismuth centres, 24,25 we recently reported the first definitive catalyst-and additive-free addition of stibines to alkenes, alkynes, ketones, and azobenzene.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent mechanistic studies into "classical" reactions involving tin hydrides have revealed fascinating complexity and paved the way to rational development of improved reaction protocols. [14][15][16][17][18][19] The addition of antimony hydrides (primary or secondary stibines) to multiple bondshydrostibination -has been explored to a very limited extent, 20, 21 with well-defined examples being restricted to cases that proceed under Lewis-acid or radical-initiator (azobisisobutyronitrile, AIBN) mediated conditions. 22,23 As part of our exploration into new structure and reactivity at antimony and bismuth centres, 24,25 we recently reported the first definitive catalyst-and additive-free addition of stibines to alkenes, alkynes, ketones, and azobenzene.…”
Section: Introductionmentioning
confidence: 99%
“…14d,f,h,i AIBN acts as a radical initiator and as an H-abstractor after the intramolecular substitution in the rearomatization step to provide the imidazolo ring; however, this transformation remains mechanistically complex. 15 Although we were gratified with the radical cyclization to deliver the desired ring systems 16a−d, we also noted developments in metallaphotoredox C(sp 2 )−C(sp 3 )-coupling of aryl bromides and alkyl bromides using TMS 3 SiH as pioneered by MacMillan and co-workers 16 and, more recently, the corresponding transformation between aryl chlorides and unactivated alkyl chlorides using the electron-rich (TMS) 3 SiNH(Adm). 17 The latter conditions were of particular interest, because our systems were comprised of alkyl chlorides and aryl halides in an intramolecular sense.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The resulting hydrogen‐bonded couple B reacts with α‐aminoalkyl radical A through RCA to form α‐carbonyl radical intermediate C . The resulting intermediate C is subjected to cyclization to give cyclohexadiene π‐radical intermediate D , which subsequently undergoes SET followed by PT or HAT with V‐70 [25h,j] to give 1,2,3,4‐THQ 5 and the hydrazyl radical. The resulting hydrazyl radical generated from the two cycles would be converted into hydrazine through SET followed by PT or HAT by the reaction with cyclohexadiene π‐radical intermediate D or Ir II .…”
Section: Resultsmentioning
confidence: 99%
“…The resulting hydrazyl radical generated from the two cycles would be converted into hydrazine through SET followed by PT or HAT by the reaction with cyclohexadiene π‐radical intermediate D or Ir II . We could not isolate the resulting hydrazine because of an unstable compound that leads to degradation products [25e–g,j] …”
Section: Resultsmentioning
confidence: 99%